Association between psychosocial factors at work and nonfatal myocardial infarction in a population-based case-control study in Czech men - Bobák, M; Hertzman, C; Skodová, Z; Marmot, M (Epidemiology (Cambridge, Mass.), 1998)
We examined the effect of decision latitude and work demand on risk of myocardial infarction in a former Soviet Bloc country and analyzed whether these factors contributed to the educational gradient in myocardial infarction in this population. We conducted a case-control study among full-time working men in the general population of five districts of the Czech Republic. Cases were 179 men 25-64 years of age with a first nonfatal myocardial infarction diagnosed in selected districts over a 1-year period, and controls were 784 men in the same age group randomly selected from the population register. We used logistic regression to estimate the odds of developing myocardial infarction in relation to self-reported work demand and decision latitude at work and the contribution of these factors as well as standard risk factors to socioeconomic differences in the risk of myocardial infarction. Cases reported lower decision latitude and lower work demand than controls. Age-adjusted odds ratios for the highest vs lowest quartiles of decision latitude and work demand were 0.43 (95% confidence interval = 0.25-0.75) and 0.54 (95% confidence interval = 0.31-0.93), respectively. Further adjustment for coronary risk factors and education did not change these estimates. Decision latitude accounted for part of the association between education and myocardial infarction, and decision latitude and risk factors jointly explained virtually all of it. The association between decision latitude at work and myocardial infarction found in our study is consistent with research in western populations and may partly explain the socioeconomic gradient in myocardial infarction.
Keywords: Logistic Models; společenská třída; Male; Social Class; Česká republika; psychický stres; Adult; Case-Control Studies; dospělí; mužské pohlaví; Decision Making; stupeň vzdělání; rozhodování; infarkt myokardu; logistické modely; Czech Republic; hygiena práce; lidé; studie případů a kontrol; Educational Status; Humans; Stress, Psychological; Myocardial Infarction; Occupational Health; lidé středního věku; Middle Aged